(untitled) (Journal of Economic Research & Business Administration, 2019)
The relevance of the title studied in the article is due to the specifics of Islamic Finance, which demonstrate their advantages and find distribution throughout the world, both in the countries of Muslim society and in developed European countries. As Islamic Finance in Kazakhstan has not been developed properly since 2009, the authors set a goal to study the experience and mechanism of better adaptation and integration of Islamic Finance in the financial sector of the country. Based on the analysis of international experience of application of Islamic financial instruments developed and proposed recommendations for enhancing their implementation and increase the impact on the real sector of the economy of the Republic of Kazakhstan. The results of the study showed that the problem of insufficient spread of Islamic banking and finance is using a more conservative model of development Islamic finance and the presence of some restrictive barriers of both prudential and social nature. Research results. The results of the study can be used for the successful spread of Islamic Finance in Kazakhstan, as well as to promote economic cooperation with the countries of the Islamic world. Application area. The results of the study can be used and applied to the successful experience of the implementation and development of Islamic Finance in Kazakhstan, and also with the economic cooperation of the countries of the Islamic world.